Challenges to the Effectiveness of Higher Education in Madagascar: An Analysis of Key Hindering Factors - Emynorane, Ralaivao Hanginiaina; Ibrahim, Muhammad Akmal; Hasniati, ‎; Yunus, Muhammad (KnE Social Sciences, 2025)
This study explores the key factors hindering the effectiveness of the higher education system in Madagascar, with a specific focus on the University of Toliara. Employing a qualitative descriptive approach, the study aims to provide an in-depth understanding of the challenges faced by both students and lecturers within the academic environment. Data were collected through in-depth interviews, direct observation, and a documentation study. The study involved 30 third-year students from the Department of Management within the Faculty of Law, Economy, Management, and Sociology (DEGS), 10 lecturers, and 3 academic staff members from the University of Toliara. The findings reveal a complex interplay of issues impacting the quality and effectiveness of higher education, including insufficient funding and infrastructure, outdated curricula, overcrowded classrooms, unequal access to higher education across regions, political instability, graduate unemployment leading to brain drain, and weak research and innovation capacity. These challenges contribute to a learning environment that struggles to meet both national development needs and international academic standards. The study emphasizes the urgent need for targeted policy reforms, increased investment, and stronger institutional support to enhance the quality, accessibility, and relevance of higher education in Madagascar.